Simplicity and savage in La Vorágine [The Vortex] and El abrazo de la serpiente [Embrace of the Serpent] - Garay Cano, Luz Adriana; Cubides Serrano, Edwin (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This paper aims a new approach to indigenous representation in literature and cinema through the intertextual analysis between La Vorágine (1924) [The Vortex] and El abrazo de la serpiente (2015) [Embrace of the Serpent]. It is concluded, after a detailed study, that both – the novel and the film, bring anew perspective from the indigenous by means of simplicity as an actual way of being of this importantcommunity in Colombia.